Detecting emphysema with multiple instance learning - Orting, Silas Nyboe; Petersen, Jens; Thomsen, Laura H.; Wille, Mathilde M W; de Bruijne, Marleen (Proceedings (International Symposium on Biomedical Imaging), 2018)
Emphysema is part of chronic obstructive pulmonary disease, a leading cause of mortality worldwide. Visual assessment of emphysema presence is useful for identifying subjects at risk and for research into disease development. We train a machine learning method to predict emphysema from visually assessed expert labels. We use a multiple instance learning approach to predict both scan-level and region-level emphysema presence. We evaluate performance on 600 low-dose CT scans from the Danish Lung Cancer Screening Study and achieve an AUC of 0.82 for scan-level prediction and AUCs between 0.76 and 0.88 for region-level prediction.